Current microbiological testing approaches and documented infections at febrile neutropenia onset in patients with hematologic malignancies - Chumbita Mariana; Peyrony Olivier; Teijón-Lumbreras Christian; Monzó-Gallo Patricia; Aiello Tommaso Francesco; Gallardo-Pizarro Antonio; Gras Emmanuelle; Puerta-Alcalde Pedro; Mateu Espasa; Martínez Carmen; Rivero Andrea; Casals-Pascual Climent; et al. (International Journal of Infectious Diseases, 2024)
Objectives: This study aims to identify infection etiology in febrile neutropenia (FN) is vital. This study explores different microbiological approaches and their impact on diagnosing infections in patients with hematologic malignancies and FN. Methods: This is a retrospective analysis conducted at the Hospital Clinic of Barcelona details microbiological testing strategies used to diagnose infections at FN onset between January 2020 and July 2022. Results: A total of 4520 microbiological tests were ordered in 462 FN episodes, achieving a 10% test positivity rate, with 200 (43.3%) episodes showing microbiological documentation of infection. Blood cultures (40.4%), non-culture blood tests (21.2%), and respiratory tract samples (16.2%) were the most requested. Blood cultures exhibited the highest (16.9%) test positivity rates, whereas non-culture blood tests showed the lowest (3.3%). Bacterial infections were present in 149 of 462 (32.3%) FN episodes. Viral infections (66 of 462, 14.3%)—notably, respiratory viruses—were also frequent. Mortality rate at 60 days was 9.1%; documented infections were associated with a higher risk (15%). Conclusions: In the current landscape of antimicrobial diagnostics, our findings revealed the highest reported rate of microbiologically documented infections at FN onset. Bacterial infections are common; however, our data reiterate the significance of viral infections in causing fever. Optimizing FN management during respiratory viral infections remains a challenge for antimicrobial de-escalation. The low positivity rates observed in certain diagnostic tests emphasize the need for cost-effective diagnostic stewardship.